Ngos Working For Education In Rajasthan: Examining the Impact of NGOs on Education and Poverty Alleviation in Rajasthan (Journal of Advances and Scholarly Researches in Allied Education, 2013)
Rajasthan is thelargest State of India in terms of total area occupied. The pattern in publicspending on education presents an encouraging picture. Though Rajasthan’s percapita income is relatively low on education, and this ratio has beenincreasing over the past decade. Furthermore, Rajasthanhas always been a home of voluntary efforts and voluntarism. The voluntarysector organizations have played a vital role in addressing the issuesconcerning the life of the poor, disadvantaged and underprivileged. Today thereare an impressive number of voluntary organizations in the state offeringalternative perspective.